Crystallization Kinetics of a Liquid-Forming 2D Coordination Polymer - Das, Chinmoy; Nishiguchi, Taichi; Fan, Zeyu; Horike, Satoshi (Nano letters, 2022)
We investigated a mechanism of crystal melting and crystallization behavior of a two-dimensional coordination polymer [Ag2(L1)(CF3SO3)2] (1, L1 = 4,4′-biphenyldicarbonitrile) upon heating-cooling processes. The crystal showed melting at 282 °C, and the following gentle cooling induced the abrupt crystallization at 242 °C confirmed by DSC. A temperature-dependent structural change has been discussed through calorimetric, spectroscopic, and mechanical measurements. They indicated that the coordination-bond networks are partially retained in the melt state, but the melt showed a significantly low viscosity of 9.8 × 10–2 Pa·s at T m which is six orders lower than that of ZIF-62 at T m (435 °C). Rheological studies provided an understanding of the fast relaxation dynamics for the recrystallization process, along with that the high T m provides enough thermal energy to crossover the activation energy barrier for the nucleation. The isothermal crystallization kinetics through calorimetric measurements with applying the Avrami equation identified the nature of the nuclei and its crystal growth mechanism.